Treatment Costs of Pneumonia, Meningitis, Sepsis, and Other Diseases among Hospitalized Children in Viet Nam - Anh, Dang Duc; Riewpaiboon, Arthorn; Tho, Le Huu; Nyambat, Batmunkh (Journal of Health, Population and Nutrition, 2010)
The aim of this study was to estimate the costs of treatment of children who present with the signs and symptoms of invasive bacterial diseases in Khanh Hoa province, Viet Nam. The study was an incidencebased cost-of-illness analysis from the health system perspective. The hospital costs included labour, materials and capital costs, both direct and indirect. Costs were determined for 980 children, with an average age of 12.67 months (standard deviation±11.38), who were enrolled in a prospective surveillance at the Khanh Hoa General Hospital during 2005-2006. Of them, 57% were male. By disease-category, 80% were suspected of having pneumonia, 8% meningitis, 3% very severe disease consistent with pneumococcal sepsis, and 9% other diseases. Treatment costs for suspected pneumonia, meningitis, very severe disease, and other diseases were US 31, US 57, US 73, and US 24 respectively. Costs ranged from US 24 to US 164 across different case-categories. Both type of disease and age of patient had statistically significant effects on treatment costs. The results showed that treatment costs for bacterial diseases in children were considerable and might differ by as much as seven times among invasive pneumococcal diseases. Changes in costs were sensitive to both age of patient and case-category. These cost-of-illness data will be an important component in the overall evidence base to guide the development of vaccine policy in Viet Nam. Key words: Cost-of-illness; Healthcare costs; Meningitis; Pneumococcal diseases; Pneumonia; Sepsis; Viet Nam DOI: 10.3329/jhpn.v28i5.6151 J HEALTH POPUL NUTR 2010 Oct;28(5):436-442